2021
DOI: 10.3390/ijms222312653
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Electric Double Layer of the Protic Ionic Liquid [Dema][TfO] Analyzed by Atomic Force Spectroscopy

Abstract: Protic ionic liquids are promising electrolytes for fuel cell applications. They would allow for an increase in operation temperatures to more than 100 °C, facilitating water and heat management and, thus, increasing overall efficiency. As ionic liquids consist of bulky charged molecules, the structure of the electric double layer significantly differs from that of aqueous electrolytes. In order to elucidate the nanoscale structure of the electrolyte–electrode interface, we employ atomic force spectroscopy, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This effect is regularly reported in literature and attributed to a decrease in stiffness of the layers as a function of distance from the charged substrate. [ 4,9,14 ] This reflects a slightly compressible structure and is often observed for intermediate charged surfaces, such as mica, [ 9 ] or less strong applied potentials. [ 4,14 ]…”
Section: Resultsmentioning
confidence: 99%
“…This effect is regularly reported in literature and attributed to a decrease in stiffness of the layers as a function of distance from the charged substrate. [ 4,9,14 ] This reflects a slightly compressible structure and is often observed for intermediate charged surfaces, such as mica, [ 9 ] or less strong applied potentials. [ 4,14 ]…”
Section: Resultsmentioning
confidence: 99%
“…2 For example, the processes of energy storage and release are closely related to the EDL structure in IL-based supercapacitors, which is composed of an inner tightly bound ion layer and an outer loose layer with alternating cations and anions. [3][4][5][6][7] The formation of either a multilayer alternating cation and an anion structure or a distinctive dense counterion monolayer in ILs across the longitudinal direction to the surface has been confirmed by both experimental 4,[6][7][8][9][10][11] and theoretical [12][13][14][15][16] studies and suggested to play a crucial role in the capacitive performance at IL-electrode interfaces. 16,17 The capacitance of ILs at the electrode surface is reported to be determined by, and reflects, the microstructural changes within the innermost region of the EDL.…”
Section: Introductionmentioning
confidence: 85%
“…26 The AFMobtained contact resonance frequency provides a good measure of the contact stiffness, 27,28 reflecting on the IL microstructural changes, in which a higher contact stiffness is indicative of more ordered ion layers 29 associated with a higher rupture force. 10 Thus, in this work, we utilized a gold colloid probe to model an electrode surface to directly capture the contact resonance frequency of the ILs at the gold electrode surface at varying biased voltages, further discerning the interfacial ion microstructure at charged surfaces. We considered two ILs with cations sharing the same cation head but possessing varying chain lengths, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For a summary of modern studies of the IL leaching (seepage) problem, we recommend the review of Ebrahimi et al (2021), in which their Section 4 and Table 3 deals specifically with the leaching issue. For a summary of modern studies of IL effects on ORR kinetics, we recommend the short review of Wippermann et al ( 2022) and add to this the mention of a newer paper by Korte et al, which noticed, using atomic force microscopy, an altered double-layer structure near a Pt (100) surface when doping [dema][TfO] with water (Rodenbücher et al, 2021).…”
Section: Other Il-pemfc Propertiesmentioning
confidence: 99%